2020
DOI: 10.1175/jcli-d-19-0679.1
|View full text |Cite
|
Sign up to set email alerts
|

Can Tropical Pacific Winds Enhance the Footprint of the Interdecadal Pacific Oscillation on the Upper-Ocean Heat Content in the South China Sea?

Abstract: In this study, an enhanced footprint of the interdecadal Pacific oscillation (IPO) on the upper-ocean heat content (OHC) in the South China Sea (SCS) since the 1990s is revealed. The negative OHC-IPO correlation is significant (r 5 20.71) during 1990-2010 [period 2 (P2)], whereas it is statistically insignificant during 1960-80 [period 1 (P1)]. Analyses show that the scope of the equatorial Pacific wind anomalies is wider during P2 compared with that during P1 due to a larger east-west SST gradient and enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 81 publications
0
10
0
Order By: Relevance
“…In addition to these periodic variations, the Karimata Throughflow heat transport also shows a significant ascending trend of 0.78 TW per year over the period of 1998–2015, suggesting reduction of heat transport from the SCS to the Java Sea by around 15 TW over the past two decades. This decreasing trend of southward heatflux is closely related to the decadal change of upper ocean heat content in the SCS associated with the Interdecadal Pacific Oscillation (IPO) (Xiao et al., 2019, 2020).…”
Section: Resultsmentioning
confidence: 98%
“…In addition to these periodic variations, the Karimata Throughflow heat transport also shows a significant ascending trend of 0.78 TW per year over the period of 1998–2015, suggesting reduction of heat transport from the SCS to the Java Sea by around 15 TW over the past two decades. This decreasing trend of southward heatflux is closely related to the decadal change of upper ocean heat content in the SCS associated with the Interdecadal Pacific Oscillation (IPO) (Xiao et al., 2019, 2020).…”
Section: Resultsmentioning
confidence: 98%
“…Abundant water exchange and complex atmospheric processes make the SCS susceptible to the Pacific and Indian Oceans but quite different from them (Liu et al, 2004;Chiang et al, 2018). Observational analyses have shown that the sea surface temperature in the SCS (SCS SST) exhibit abundance of multiple timescales from seasonal to decadal variabilities, which are largely modulated by the East Asian monsoon, El Niño-Southern Oscillation (ENSO), Interdecadal Pacific Oscillation, and global warming (Shen and Lau, 1995;Tomita and Yasunari, 1996;Ose et al, 1997;Chu et al, 1999;Klein et al, 1999;Qu, 2001;Chen et al, 2003;Wang et al, 2006a;Yu and Qu, 2013;Wu et al, 2014;Cheng et al, 2016;Cheng et al, 2017;Cheng et al, 2019;Xiao et al, 2020a;Liang et al, 2021). Among them, the impact of ENSO on the SCS SST on the interannual timescale has been widely studied.…”
Section: Introductionmentioning
confidence: 99%
“…Its sea surface temperature (SST) also presents a significant seasonal cycle, and air-sea heat flux plays a leading role while ocean circulation advection plays a secondary role (Qu, 2001). The SCS temperature interannual variability and long-term change have been widely studied, and the circulation advection effect is one of the major contributions (Wang, 2002;Liu et al, 2004Liu et al, , 2014Xiao et al, 2018Xiao et al, , 2020. Additionally, the surface heat fluxes are also key factors modulating the SST anomalies in the SCS (Wu et al, 2014;Wang and Wu, 2021).…”
Section: Introductionmentioning
confidence: 99%